Using contextual teaching and learning (CTL) approach to improve students' speaking ability - Ramzi Yusyac; Asnawi Muslem; Burhanuddin Yasin (Universitas Syiah Kuala, 2021)
The objective of this research is to investigate the implementation of Contextual Teaching and Learning (CTL) to improve students’ speaking skills in the aspects of accuracy, clarity, and fluency. This research employed a quantitative method in nature. A pre-experimental design with pre-test and post-test was used. The population of this research was all second-year students. The sample of this research was one of the second-year classes chosen by using the purposive sampling technique. The instrument used in this research was a speaking test: pre-test and post-test. The data collected were analyzed statistically. The results showed that the implementation of contextual teaching and learning (CTL) improved students’ speaking skills in terms of accuracy, clarity, and fluency. The result of Wilcoxon showed the value of Asymp. Sig (2-tailed) for accuracy, clarity, and fluency is 0.000 which means that the resulting test is less than the minimum requirements of the statistics range (0.05). Therefore, the use of CTL in teaching and learning speaking is very beneficial for students to improve their speaking skills. Thus, the hypothesis of this research was accepted. There is a significant improvement in students’ speaking skills after they were taught by using CTL.